Investing in Water: Assessing the Feasibility of Implementing a Water Sharing Investment Partnership in Texas' Rio Grande Water Market - Lynch, Lauren. (2017)
Abstract: Across the globe, freshwater ecosystems are facing unprecedented threats as increasing demands from agriculture, industry and growing metropolitan centers put pressure on limited water supplies. In the American West, recurring drought and dramatic population growth have lead to persistent water shortages throughout the past century. This thesis focuses on water scarcity in Texas' Rio Grande basin and explores the feasibility of implementing market-based solutions to ensure that sufficient water is allocated to local freshwater ecosystems. Specifically, this study evaluates a market-based water conservation model developed by The Nature Conservancy in 2015, Water Sharing Investment Partnerships (WSIP), and assesses the feasibility of implementing this model in Texas' Rio Grande water market. Through document analysis, stakeholder interviews, GIS mapping and site visits, the results of this study indicate that Texas' Rio Grande water market shows promise as a location in which a future WSIP may be feasible.; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Barbara Parmenter, and Scott Horsley.; Keywords: Water resources management, Environmental economics, and Environmental management.